(3OQjGb GdCaGYi aj GdQO Ydi GdNGQL GdHbGYis - (3eMeO Hf LeYI GdMUcajs ((3MSf Hf fHgGf s)
(3ChdgG (B:s
" (3Chef cGf ejJkG aCMjjfGg hLYdfG dg fhQkG jeTi Hg ai GdfGS cef eKdg ai GdXdeGJ djS HNGQL efgG cPdc Rjf ddcGaQjf eG cGfhG jYedhf (B" s
(3BNQgG (B:s
(3SGFQ ef JYfi ef ChdjGA Gddg JYGdi hUdi Gddg Ydi SjOfG eMeO hBdg s
(3GdfSNI HgG MhGTs
(3QO ajg GdeDda Ydi GdHbGYi hGfJUQ ajg dGHf GdaGQVs
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdBUajI HMjOQ CHGO (B((3cdGe (B140) s
Keywords: (3GdJhMjO hGdedd hGdfMds